2017
DOI: 10.5195/jmla.2017.109
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based information needs of public health workers: a systematized review

Abstract: ObjectiveThis study assessed public health workers’ evidence-based information needs, based on a review of the literature using a systematic search strategy. This study is based on a thesis project conducted as part of the author’s master’s in public health coursework and is considered a systematized review.MethodsFour databases were searched for English-language articles published between 2005 and 2015: PubMed, Web of Science, Library Literature & Information Science Index, and Library, Information Science & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 51 publications
(288 reference statements)
0
31
0
1
Order By: Relevance
“…To achieve a stronger practice orientation, besides more consistent evaluation of programs, we need research that better responds to practitioners’ needs and circumstances (e.g., practice-based research networks) (81), funding mechanisms that evaluate natural experiments (26), and reliance on so-called “tacit knowledge” or “colloquial evidence” (pragmatic information based on direct experience and action in practice) (117, 164). Among practitioners, the general concepts and importance of EBPH are well accepted; there is less clarity on the definition of evidence, how to find it, how to use it (7) and how to weight the variations among types or sources of evidence, recognizing that decisions should be based not just on the strength of evidence, but also on the weight of evidence (84). These observations highlight the need for clarity in the criteria for sufficient evidence to catalyze action as well as capacity-building activities for both those sponsoring the intervention and the target organizations and populations.…”
Section: Why Evidence-based Public Health Mattersmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve a stronger practice orientation, besides more consistent evaluation of programs, we need research that better responds to practitioners’ needs and circumstances (e.g., practice-based research networks) (81), funding mechanisms that evaluate natural experiments (26), and reliance on so-called “tacit knowledge” or “colloquial evidence” (pragmatic information based on direct experience and action in practice) (117, 164). Among practitioners, the general concepts and importance of EBPH are well accepted; there is less clarity on the definition of evidence, how to find it, how to use it (7) and how to weight the variations among types or sources of evidence, recognizing that decisions should be based not just on the strength of evidence, but also on the weight of evidence (84). These observations highlight the need for clarity in the criteria for sufficient evidence to catalyze action as well as capacity-building activities for both those sponsoring the intervention and the target organizations and populations.…”
Section: Why Evidence-based Public Health Mattersmentioning
confidence: 99%
“…For public health practitioners to apply the latest scientific evidence, they need to be connected all along the research production-to-application pipeline, and not just the end of it (7, 81). Research-based evidence serves many public health functions including assuring the public and policymakers of the scientific grounding of advice, selecting EBIs, needs assessment, evaluation, and grant writing (102).…”
Section: Why Evidence-based Public Health Mattersmentioning
confidence: 99%
“…Workload pressures and accessibility of peer reviewed publications are often cited as barriers to uptake of research evidence by commissioners (1,2). In addition to time constraints and accessibility, practitioners may lack the skills to nd, appraise and synthesise relevant evidence (3). The role of evidence-brie ng services and information professionals is to nd evidence relevant to local context and needs, and present them to commissioners as concise, actionable points (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…lack of systems dedicated to EBP application and dissemination). [12][13][14][15] A 2010 study of PHNs identified needs for resources that are easily navigable and well organised for their specific information needs. 16 According to Krom et al, 17 nurses lack an awareness of electronic databases and how to navigate them effectively.…”
Section: Introductionmentioning
confidence: 99%